Perencanaan dan Strategi Pemasaran Asuransi - Mei Habibah Dalimunthe; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
The purpose of this article is to find the marketing plans and strategies that a company needs to develop its business. Because, as we know, the challenges for the Indonesian insurance industry are increasing with the number of foreign insurance companies, which is a direct result of globalization. In the next era, called globalization, Indonesian insurance / reinsurance companies will work to develop their insurance business with the